Melt generation and evolution in the Adda’do rift segment of the Afar rift from trace elements and petrography - Rhiannon Rees; Rhiannon Rees; Emma J. Watts; Emma J. Watts; Thomas M. Gernon; Rex N. Taylor; Carolina Pagli; Derek Keir; Derek Keir (Frontiers in Earth Science)
Along-rift variations in the stage of continental separation are observed in the northern East African Rift System (EARS), from magma-assisted continental rifting in the Main Ethiopian Rift (MER) to nascent oceanic spreading in Afar. However, the implications on spatial and temporal changes in mantle melting and melt evolution remain poorly understood. Given that the EARS is the longest and best-exposed example of continental rifting in the world, the MER and Afar are an ideal place to investigate magmatism and volcanism in late-stage continental rifts. Here, we focus on the Adda’do Magmatic Segment (AMS) in the northernmost sector of the MER, that has experienced the most prolonged lithospheric thinning. We present new trace element data and petrographic observations from around 50 samples, and combine these with geochemical modelling to investigate depth of melt origin and melt evolution, in the AMS. Using mixing modelling of garnet lherzolite and spinel lherzolite mantle peridotite sources, we show that the AMS magmas are produced from a relatively deep source with 10%–60% garnet lherzolite, corresponding to depths of around 85 km, and generated by approximately 4%–9.5% partial melting of the mantle. We find no significant variation of these characteristics with either sample age or sample location at the AMS, suggesting no systematic temporal variations occurred in either the depth or the degree of melting within a single magmatic segment. However, on a regional scale, depth of melting is between that interpreted for the MER and northern Afar, implicating the stage of rift evolution and consequent degree of lithospheric thinning as a major control. MELTS modelling of the samples indicates that the observed variations in sample compositions in the AMS can be explained predominantly by fractional crystallisation, with negligible crustal contamination in the basaltic samples. Crustal contamination may play a greater role in the composition of intermediate and evolved samples in the AMS.